ANALYSIS OF CO-OCCURRENCE OF AUTISM SPECTRUM DISORDER WITH OTHER NEUROLOGICAL DISORDERS - CHANDRAKALA, ELUMALAI; NAGARAJ, KAKANAHALLI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study explores the co-occurrence of autism spectrum disorder (ASD) with associated disorders such as epilepsy, attention deficit hyperactive disorder (ADHD), Down’s syndrome (DS), and cerebral palsy (CP). Methods: This cross-sectional study was carried out in special schools of four districts in Karnataka. A total of 49 ASD individuals were identified among 552 developmentally challenged children. ASD individuals were screened for associated neurological disorders and segregated the data as ASD, ASD with epilepsy, ASD-epilepsy-ADHD, ASD with DS, and ASD with CP. The karyotype analysis was carried out for chromosomal anomalies. Results: It is found that 57% of the individuals showed only ASD features and the remaining 43% shared ASD features with other neurological disorders. Among 43% of comorbidity, 35% of ASD individuals have epilepsy, 2% have epilepsy-ADHD, 4% have DS, and 2% have CP. Conclusion: This study supports the strong association between ASD with epilepsy, DS, ADHD, and CP. However, the extent of association of ASD with epilepsy is higher than other neurological disorders. As both are complex neurological disorders, they both show intellectual disability and involve multiple genetic factors. The present investigation is the unique and first report of this study region and also supports earlier studies, suggesting that there is an association of ASD with other neurological disorders.